2019
DOI: 10.1124/jpet.118.252759
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as a Novel Therapeutic Target for Friedreich’s Ataxia

Abstract: Friedreich ataxia (FRDA) is a progressive neuro-and cardiodegenerative disorder characterized by ataxia, sensory loss, and hypertrophic cardiomyopathy. In most cases, the disorder is caused by GAA repeat expansions in the first introns of both alleles of the FXN gene, resulting in decreased expression of the encoded protein, frataxin. Frataxin localizes to the mitochondrial matrix and is required for iron-sulfur-cluster biosynthesis. Decreased expression of frataxin is associated with mitochondrial dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 27 publications
3
97
0
Order By: Relevance
“…Along this line, we found a decrease of NRF2 and GPX4, altered expression of genes controlling iron metabolism and increased susceptibility to ferroptosis in brown adipocyte precursors, as well as in mature adipocytes isolated from KIKO mice. These results are in accordance with the findings pointing to oxidative stress, iron overload, and ferroptosis among the main pathogenic factors in FRDA 6,27,[53][54][55] . Interestingly, NRF2, besides being an up-stream modulator of the expression of antioxidant genes and protection against oxidative stress/ferroptosis 56,57 , positively regulates enzymes involved in mitochondrial oxidation of FAs 29 and adipogenesis 58,59 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Along this line, we found a decrease of NRF2 and GPX4, altered expression of genes controlling iron metabolism and increased susceptibility to ferroptosis in brown adipocyte precursors, as well as in mature adipocytes isolated from KIKO mice. These results are in accordance with the findings pointing to oxidative stress, iron overload, and ferroptosis among the main pathogenic factors in FRDA 6,27,[53][54][55] . Interestingly, NRF2, besides being an up-stream modulator of the expression of antioxidant genes and protection against oxidative stress/ferroptosis 56,57 , positively regulates enzymes involved in mitochondrial oxidation of FAs 29 and adipogenesis 58,59 .…”
Section: Discussionsupporting
confidence: 92%
“…Ferroptosis is a form of ironmediated and lipid-mediated programmed cell death recently implicated in neurodegenerative diseases including FRDA. Notably, increased susceptibility to ferroptosis was found in primary patient-derived fibroblasts and murine fibroblasts from a mouse FRDA model 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In FRDA, the expression of the encoded protein frataxin was decreased, leading to obstruction of mitochondrial matrix iron-sulfur cluster biosynthesis, mitochondrial dysfunction, and mitochondrial iron accumulation, and finally result in increased oxidative stress. Studies have found that cells treated with ferric ammonium citrate (FAC) and L-buthionine-sulfoximine (BSO) consistently show reduced GSH-dependent peroxidase activity and increased lipid peroxidation in FRDA disease model (Cotticelli et al, 2019). When comparing the erastin in the induction of ferroptosis in neurons and HT1080 fibrosarcoma cells, it was found that selective protection of neurons by class I histone deacetylase (HDAC) inhibitors and accelerated cancer cell ferroptosis (Zille et al, 2019).…”
Section: Ferroptosis In Other Neurodegenerative Diseasesmentioning
confidence: 99%
“…Also, it has been demonstrated that ferroptosis is an important cell death pathway for dopaminergic neurons that is regulated by protein kinase C in PD, and that autophagy contributes to ferroptosis by the degradation of ferritin . Ferroptosis has also been considered as a novel therapeutic target for Friedreich's Ataxia, AD, and HD . Since the discovery of the ferroptosis, iron, and ROS have been increasingly acknowledged as crucial initiators and mediators of cell death in a variety of organisms and pathological situations.…”
Section: Brain Iron Misregulation Is a Common Pathway In Neurodegenermentioning
confidence: 99%